2008
DOI: 10.1074/jbc.m801713200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of 5-HT2A/C Receptors Counteracts 5-HT1A Regulation of N-Methyl-D-aspartate Receptor Channels in Pyramidal Neurons of Prefrontal Cortex

Abstract: Abnormal serotonin-glutamate interaction in prefrontal cortex (PFC) is implicated in the pathophysiology of many mental disorders, including schizophrenia and depression. However, the mechanisms by which this interaction occurs remain unclear. Our previous study has shown that activation of 5-HT 1A Serotonin (5-HT)2 is a key neuromodulator mediating diverse cognitive and emotional functions in the central nervous system (1). The pleiotropic functions of serotonin are afforded by the concerted actions of mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 54 publications
2
79
1
2
Order By: Relevance
“…In order to evaluate the role of serotonergic system, the receptor subtypes 5HT-1A, 5HT-2A, and 5HT-2C were specifically selected for gene analysis. The selection was based on the role that those receptors play in regulating the 5HT firing and their involvement in the pathophysiology of schizophrenia (Jensen et al, 2010;Simpson et al, 1996;Yasuno et al, 2003;Yuen et al, 2008). Our results indicate that the expression of 5HT-1A receptor was induced by about twofold in response to the chronic ketamine treatment in the cortex tissues (Figure 10).…”
Section: Antipsychotic Effects Of Bacopa Monnera 1855mentioning
confidence: 58%
“…In order to evaluate the role of serotonergic system, the receptor subtypes 5HT-1A, 5HT-2A, and 5HT-2C were specifically selected for gene analysis. The selection was based on the role that those receptors play in regulating the 5HT firing and their involvement in the pathophysiology of schizophrenia (Jensen et al, 2010;Simpson et al, 1996;Yasuno et al, 2003;Yuen et al, 2008). Our results indicate that the expression of 5HT-1A receptor was induced by about twofold in response to the chronic ketamine treatment in the cortex tissues (Figure 10).…”
Section: Antipsychotic Effects Of Bacopa Monnera 1855mentioning
confidence: 58%
“…It is noteworthy that M100907 and pimavanserin effectively block the effects of acute PCP stimulation of locomotor activity, considered a model of psychosis (Maurel-Remy et al, 1995;Vanover et al, 2006;Gardell et al, 2007) as well as their ability to block NMDA antagonist effects on the firing rate of pyramidal neurons (Wang and Liang 1998). The 5-HT 2A receptor has been shown to play a key role in the transport and dynamic regulation of NMDA receptors in cortical pyramidal neurons (Yuen et al, 2008). 5-HT 2A agonists which are hallucinogens modulate NMDA receptor-mediated neurotransmission in the prefrontal cortex, effects that are blocked by M100907 (Arvanov et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…They observed that although Met-enkephalin, etorphine, and methadone result in the robust desensitization of Metenkephalin-induced hyperpolarization and internalization of the receptor in locus ceruleus neurons expressing FLAG-tagged ORs, oxycodone is unable to promote either event, whereas the agonists morphine and oxymorphine both induce receptor desensitization without detectable internalization. Although desensitization and internalization may be interrelated, particularly because receptor sequestration into intracellular vesicles can disrupt further coupling between the receptor and certain downstream effectors, internalization has been shown to facilitate receptor signaling to additional signaling cascades for other GPCRs (Luttrell et al, 1997;Daaka et al, 1998;Lin et al, 1998;Yuen et al, 2008). Therefore, internalization and desensitization cannot reliably be considered as synchronous events.…”
Section: Biased Agonism With Respect To Receptor Internalizationmentioning
confidence: 99%